O REINO DE CRISTO E O REINO DO ANTICRISTO NO POEMA O GRANDE INQUISIDOR , DE DOSTOIÉVSKI - Golin, Luana Martins (2011)
Dostoevsky presents a criticism to materialism, power, and authority as constraint in The Grand Inquisitor . It is not possible to neglect that in this work he warns us of any kind of regime that suppresses freedom and hides suffering on behalf of human justice and happiness in order to turn human being into manipulable objects. Dostoevsky was influenced by Eastern Orthodox Mysticism and according to him freedom is the mark of God in human being. Freedom denying, as well as proposed in inquisitor antichrist kingdom, implicates a divine detachment which leads to nihilism. Thereby, the way proposed by Dostoevsky is of facing and accepting this tragic freedom, which is only fully experienced in Christ and at love practicing.